In vitro combination effects of vancomycin and .BETA.-lactams against methicillin-resistant Staphylococcus aureus - Jinushi Yutaka; Kimura Yoshiji; Munekage Tadashi; Yoshida Isamu; Sasaki Shimaru (Japanese Journal of Chemotherapy, 1999)
We determined the in vitro combination effects of vancomycin (VCM) plus flomoxef (FMOX), VCM plus cefpirome (CPR), and VCM plus imipenem (IPM) by the checkerboard method on 560 methicillin-resistant Staphylococcus aureus (MRSA), which were clinically isolated in 1995, 1996 and 1997, and compared their MICs and fractional inhibitory concentration (FIC) index. For these three years, the antibacterial activities of VCM alone showed high levels against the 560 MRSA with the same MIC90 of 1μg/ml, and no strains detected of MIC with more than 4μg/ml. During the same period, each β-actam alone demonstrated the same antibacterial activities with the same MIC90 of 128μ/ml, 64μg/ml and 64μg/ml to FMOX, CPR and IPM, respectively. Combinations of VCM plus FMOX and of VCM plus IPM displayed synergistic effects, an FIC index of≤0.5 against more than 90% of the strains, and additive effects, an FIC index from >0.5 to <2.0 against all other strains. The combination of VCM plus CPR led to additive effects against most strains. None of the combinations showed antagonistic effects, an FIC index of ≥2.0, against any of the strains. By comparing the bactericidal activities against MRSA, the combinations of 0.5μg/ml VCM plus 2, 4 and 8μg/ml FMOX showed higher activities than that of each antibiotic alone. These results suggest that combination therapies of VCM plus FMOX and of VCM plus IPM can be useful in the treatment of MRSA infection. 1995年～1997年の3年間に臨床分離されたmethicillin-resistant Staphylococcus aureus (MRSA) 560株に対するvancomycin (VCM) とflomoxef (FMOX), cefpirome (CPR) およびimipenem (IPM) のβ-ラクタム薬とのin vitro併用効果をchecker board法により測定しMICおよびfractional inhibitory concentration index (FIC index) を求め検討した。MRSA 560株に対するVCM単剤のMICはMIC90値で3年間とも1μg/mlを示し, 4μg/ml以上を示す菌株は1株もなかった。β-ラクタム薬単剤の感受性も3年間で変化はなく, MIC90値はFMOX 128μg/ml, CPR 64μg/mlおよびIPM 64μg/mlを示した。最小FIC indexの検討では, VCMとFMOXおよびVCMとIPMの組み合わせではそれぞれ90%以上の菌株に対して各年度ともにFIC indexが0.5以下の相乗効果が認められ, 残りの菌株はすべて, FIC index 0.5から1.0以下の相加効果を示した。VCMとCPRの組み合わせでは多くの菌株に対して相加効果を示した。また, いずれの組み合わせにおいてもFIC indexが2.0以上の不関および拮抗作用を示す菌株は認められなかった。VCMとFMOXの併用による一定濃度殺菌作用ではVCM 0.5μg/mlとFMOX 2, 4, 8μg/mlを併用した場合にVCM単剤に比べ殺菌作用に増強がみられ, 殺菌作用の面からも併用効果が認められた。これらの成績からVCMとFMOXおよびVCMとIPMの併用はMRSA感染症の治療に有効であることが示唆された。